1994
DOI: 10.1021/j100062a031
|View full text |Cite
|
Sign up to set email alerts
|

Two-Laser Photochemistry of Phenothiazine in Solution: Ionization and Bond Cleavage from Upper States

Abstract: The one (308 nm)-and two (308 plus 480 nm)-laser photochemistry of phenothiazine in nitrogen-saturated acetonitrile and cyclohexane was investigated. The lowest excited triplet state (TI) of phenothiazine was efficiently generated following 308-nm excitation in both acetonitrile and cyclohexane. In cyclohexane, generation of the phenothiazine neutral radical via homolytic N-H bond cleavage from SI accompanied intersystem crossing. In acetonitrile, photoionization via the singlet manifold yielding the cation ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0
1

Year Published

1995
1995
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 2 publications
4
31
0
1
Order By: Relevance
“…27 Under strong irradiation conditions, the phenothiazine derivates in aqueous solution form oxidation products, even at low concentrations of drug. 28,29 In our case, we have observed that the degradation product shows a slight fluorescence band around 364 nm. The use of fresh and stirred solutions assures that its contribution to the overall PTZ fluorescence can be considered negligible at the experimental conditions.…”
Section: Photophysical Propertiessupporting
confidence: 53%
“…27 Under strong irradiation conditions, the phenothiazine derivates in aqueous solution form oxidation products, even at low concentrations of drug. 28,29 In our case, we have observed that the degradation product shows a slight fluorescence band around 364 nm. The use of fresh and stirred solutions assures that its contribution to the overall PTZ fluorescence can be considered negligible at the experimental conditions.…”
Section: Photophysical Propertiessupporting
confidence: 53%
“…1. It is assigned to 3 PTH * (E T , 60.4 kcal/mol) [29] because of its drastically reduced lifetime in the presence of dissolved oxygen [19,30]. The energy transfer experiments with anthracene (E T , 42.6 kcal/mol) and ferrocene (E T , 38.0 kcal/mol) also support this conclusion.…”
Section: Laser Flash Photolysis In Acetonitrilementioning
confidence: 92%
“…In acetonitrile, the pK a of PTH +Å is estimated low (pK a % 1.0) relative to that of diphenylamine (pK a = 1.8), as determined by M. Jonsson [26], it then mainly decays by deprotonation to give the long-lived PT Å . In addition, the energy of exciting photon of 355 nm and also that of S 1 state is higher than the N-H bond dissociation energy (3.47 eV) [30], photodissociation of the N-H bond is energetic possible. Since the radical ions yields are low due to low excitation energy of 355 nm pulses, their absorptions appear only as shoulders.…”
Section: Laser Flash Photolysis In Acetonitrilementioning
confidence: 99%
See 1 more Smart Citation
“…The laser flash photolysis system has been described in detail elsewhere. 47 Briefly, for kinetic studies and transient absorption spectra, solutions were prepared SCHEME 1 at concentrations sufficiently large to give absorbances in the range 0.6-0.8 at the excitation wavelength. Unless otherwise noted, the solutions, contained in a reservoir, were continuously purged with a stream of nitrogen and were caused to flow through a specially constructed quartz cell (7 mm × 7 mm) by means of a peristaltic pump.…”
Section: Methodsmentioning
confidence: 99%